The Effects of Microfinance Services on the Growth of Small and Medium Enterprises in Machakos County - Mwewa, Naomi Mbithe (My University, 2013)
The Small and Medium Enterprise (SME) sector has continued to play an important role in Kenyan Economy. The sector’s contribution to the Gross Domestic Product (GDP) increased from 13.8% in 1993 to over 18% in 1999. The Economic survey 2012 estimated that the contribution to the GDP by this sector currently stands at over 25%. It is the objective of every entrepreneur to grow their businesses into large enterprises. To achieve this, most of the entrepreneurs make use of microfinance services. Many studies have been done in Kenya on SMEs and how they are influenced by microfinance services but none had focused on the effects of microfinance services on the growth of the SMEs. The purpose of this study was to find out the effects of microfinance services on the growth of Small and Medium Enterprises in Machakos County. A quantitative descriptive design was used to study 8 types of business categories in Machakos County. Structured questionnaire was used to collect data from 100 businesses. The sample of 100 businesses from a list of 5311 was taken as a representative population in the county. The study was on dependent and independent relationship. A moderate multiple regression analysis was used. A multivariate regression model was applied to determine the relative importance of each of the three variables; microcredit, micro insurance and training, with respect to the effects of microfinance services on the growth of SMEs. The regression analysis conducted established that two of the independent variables have a positive correlation with the dependent variable. Micro credit and training contribute positively to the sales growth while micro insurance affects growth negatively. The ANOVA analysis was intended to investigate whether the variation in the independent variables explains the observed variance in the outcome – in this study the annual growth in turnover. ANOVA findings in this study showed that there was correlation between the predictor variables (Microcredit, Micro insurance and Training provided by MFIs) and response variable (Annual growth in turnover) since P- value of 0.011 is less than 0.05. This indicated that there was a strong positive relationship between the study variables.
A MANAGEMENT RESEARCH PROJECT SUBMITTED IN PARTIAL FULFILMENT OF THE REQUIREMENTS OF THE AWARD OF MASTERS OF BUSINESS ADMINSTRATION (MBA), SCHOOL OF BUSINESS, UNIVERSITY OF NAIROBI
Keywords: Micro and Small Enterprise; Large Scale Enterprises; Small and Medium Enterprises